The effectiveness of a cooperative learning technique in influencing students' achievement in the English language subject - Sugassni, Ramachandaram (2011)
This quantitative study aims to discuss the effectiveness of a cooperative learning (CL) technique in influencing students' achievement in the English Language classroom. The study explores the use of Jigsaw II learning method in the classroom. Sixty primary school children from Year 5 in a rural school in Sabah were the participants of this study. Data were collected by giving them pre-test before teaching using Jigsaw II and post-test at the end of the study. The findings from the study suggest that the students benefited from the implementation of CL in their classroom. The results of this study revealed that using CL to teach students English Language is beneficial and effective in helping to improve their achievement. Besides that, it was also found from this study that the female students obtained better results in the CL classroom compared to their male classmates. The value of this study is to suggest the use of cooperative learning in the classroom, particularly in English language teaching and learning